Methanol Dehydration to Dimethyl Ether over Modified γ-Al2O3 with Acid, Base and Zeolite (NaA and NaX) - Maria Ulfah; Hendra Suherman; Melia Laniwati; IGBN Makertihartha; Subagjo Subagjo (Department of Chemical Engineering, Universitas Gadjah Mada, 2020)
The effect of acids, bases, zeolite NaA and zeolite NaX impregnation to g-Al2O3 on the catalyst characteristics and activity against methanol dehydration reaction were investigated. The catalyst characteristics include N2 physisorption, X-ray diffraction (XRD), and temperature-programmed desorption of ammonia (NH3-TPD) in addition to catalytic dehydration of methanol performed in a micro fixed-bed reactor at 270°C and 1 atm. The results of XRD characterization showed no changes related to the modification of alumina over acids, bases, and zeolite NaA and zeolite NaX. Therefore, the modification did not have any effect on the crystalline structure of alumina. The textural and surface acidity of g-Al2O3 changed post addition of acids, bases, zeolite NaA and zeolite NaX. NH3-TPD analysis results demonstrated that synthesized g-Al2O3 has three types of acid sites: weak, medium, and strong; however, the weak acid sites were not observed on alumina catalysts modified phosphate, KOH, zeolite NaA, and zeolite NaX. Furthermore, the concentration of strong acid sites increased in the catalyst containing KOH. The catalytic test results showed that the untreated g-Al2O3 catalyst gave prominent activity in dehydration of methanol compared to the treated catalyst following the number and strength of acid sites.